Customers’ emotions in real time: measuring affective responses to service and relationship quality at the reception desk - Nordhorn, C.; Scuttari, A.; Pechlaner, Harald (Emerald Group Publishing Ltd., 2018)
© 2018, Emerald Publishing Limited. Purpose: The purpose of this paper is to explore customers’ emotions during a host–guest interaction at the reception desk of a hotel. Guests’ emotional responses are analyzed in real time to understand their link to behavior and levels of service and relationship quality. Design/methodology/approach: To achieve this aim, 225 random customers experience six different types of interactions (scenarios) at a staged reception desk, representing a high/low service or relationship quality. The emotions provoked within guests are (video) recorded and analyzed with the help of SHORETM, a facial recognition software that processes four basic emotions derived from human muscular activity and calculates average emotional scores per scenario. Findings: Results reveal that customers respond more positively to service than to relationship quality. Informal approaches to interacting with guests are mixed; they can both excite or irritate customers. As with existing evidence in service marketing research, the results found out through this study demonstrate that a good service recovery process seems to immediately generate more satisfied customers than do constant high-quality standards. Research limitations/Implications: The main limitations are related to the semi-staged nature of social interactions, which might cause distortions in measuring emotions and limitations in the comparability of cases. Practical Implications: Practical implications are directed to service designers and managers in hospitality to improve service design and ensure effective service recoveries. Originality/value: This paper introduces a novel approach for assessing host–guest interactions in tourism based on a real-time emotional assessment of service and relationship quality in hospitality. Technologically advanced observation techniques enable in-depth analyses of actions and emotional responses between hosts and guests across time. New insights concerning service design and service recovery management are gained for practitioners and for future research.